Comparison between Temperature Gradient Gel Electrophoresis of Bacterial 16S rDNA and Diatom Test for Diagnosis of Drowning1. Issue 3 (2nd August 2017) - Idota, Nozomi; Tsuboi, Hajime; Takaso, Marin; Tojo, Misa; Kinebuchi, Takako; Nakamura, Mami; Ichioka, Hiroaki; Shintani‐Ishida, Kaori; Ikegaya, Hiroshi
Abstract: When a body is discovered in water, it is difficult to conclude whether the cause of death was drowning, even today. Although diatom testing by the digestive method is classical, we hypothesized that aquatic bacteria, as well as diatoms, might be detected in drowned bodies, and conducted temperature gradient gel electrophoresis (TGGE)‐targeting 16S rDNA. DNA was extracted from the site water, and from heart blood and liver samples from 27 bodies concluded as drowning deaths by autopsy and subjected to TGGE after amplification of 16S rDNA by polymerase chain reaction. We observed whether the feature point of each 16S rDNA from the site water and blood or liver samples matched. Considerably higher correspondence was observed in drowned bodies, and the rate was higher than that achieved with the digestive method. Moreover, TGGE is safer than the digestive method. Our study suggests that this method can aid diagnosis of drowning.